Development of web-based general biology content on the GEN-BIO platform - Prayitno, Trio Ageng; Hidayati, Nuril; Sunuyeko, Nurcholis (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
The development of valid online learning media is currently very necessary in supporting the biology learning process. A high percentage of students had misconceptions about general biology material in biology education (75%), a high percentage of student responded that are difficult to get valid general biology material on the internet (40.2%), and a high percentage of student responded so that lecturers make valid general biology material (94.1%), and the high percentage of student responses so that general biology material can be in the form of a web app (70.6%). The research objective is to produce a web app-based general biology content form on the GEN-BIO platform that meets the valid criteria. The method used in this research is R&D with the Thiagarajan development model consisting of define, design, and develop. While the disseminate will be carried out in the next research using a quasi-experimental method. The research instrument used was a needs analysis sheet in the form of a G-form given to 100 respondents, a Semester Lecture Plan (SLP) analysis sheet, a material expert validation sheet given to one lecturer, a media expert validation sheet given to one expert, a practitioner validation sheet given to give to one lecturer, and the readability test sheet given to 43 students. All instruments used in this study have been declared valid by the evaluator. Research data is a score of validity in the form of quantitative data and complementary information in the form of qualitative data. The data analysis technique used is descriptive quantitative. The results showed that it has been produced general biology content based on the web app on the GEN-BIO platform has been declared valid from material elements (98.06%), media elements (94.47%), practitioners (95.33%) and student readability (34.02% strongly agree, 57.93% agree). The research concludes that the general biology content based on the web app on the GEN-BIO platform is suitable for offline and online learning in general biology courses in Higher Education, especially in the Department of Biology Education and the Department of Biology.